Association of high waist-to-height ratio with functional outcomes in patients with acute ischemic stroke: A report from the ACROSS-China study. Issue 13 (March 2017) - Yu, Ping; Pan, Yuesong; Zheng, Huaguang; Wang, Xianwei; Yan, Hongyi; Tong, Xu; Jing, Jing; Zhang, Xiao; Guo, Li; Wang, Yilong
Abstract : Abstract: The aim of our study was to investigate the relationship between the waist-to-height ratio (WHR) and all-cause mortality and functional outcomes after acute ischemic stroke in a prospective cohort study. A total of 2076 patients (36.66% females) with ischemic stroke were analyzed from ACROSS-China, which is a nationwide, prospective, hospital-based stroke registry aimed to detect the glucose abnormality in China. One-year follow-up evaluation was done by telephone interview. Outcome measures were all-cause mortality and functional outcome defined as modified Rankin score being 6 and from 0 to 6, respectively. We identified predictors for functional outcomes using logistic regression analysis, and mortality outcome using Cox proportional hazards model which incorporated covariates with P value of < 0.2 in the univariate analysis and those of clinical importance. The higher WHR was associated with worse functional outcome, but not predictive of the patients' mortality outcomes. Compared with the first quartile (⩽0.48), the fourth quartile of the WHR was more likely to be associated with poor functional recovery (fourth quartile (≥0.56), OR = 1.38, CI: 1.08–1.77, P = 0.01; third quartile OR = 1.10, CI: 0.86–1.40, P = 0.45; second quartile OR = 1.05, CI: 0.83–1.33, P = 0.71). Our findings suggest that abdominal fat accumulation may be associated with functional recovery after stroke, and is not associated with mortality after stroke. Compared with the lowest quartile, the highest quartile of WHR at admission was possibly associated with worse postacute ischemic stroke functional recovery.